Pre-arrayed Pan-AAV peptide display libraries for rapid single-round screening - Börner, Kathleen; Kienle, Eike; Huang, Lin-Ya; Weinmann, Jonas; Sacher, Anna; Bayer, Philipp; Stüllein, Christian; Fakhiri, Julia; Zimmermann, Laura; Westhaus, Adrian; Beneke, Jürgen; Beil, Nina; et al. (Molecular therapy, 2020)
Display of short peptides on the surface of adeno-associated viruses (AAVs) is a powerful technology for the generation of gene therapy vectors with altered cell specificities and/or transduction efficiencies. Following its extensive prior use in the best characterized AAV serotype 2 (AAV2), recent reports also indicate the potential of other AAV isolates as scaffolds for peptide display. In this study, we systematically explored the respective capacities of 13 different AAV capsid variants to tolerate 27 peptides inserted on the surface followed by production of reporter-encoding vectors. Single-round screening in pre-arrayed 96-well plates permitted rapid and simple identification of superior vectors in >90 cell types, including T cells and primary cells. Notably, vector performance depended not only on the combination of capsid, peptide, and cell type, but also on the position of the inserted peptide and the nature of flanking residues. For optimal data availability and accessibility, all results were assembled in a searchable online database offering multiple output styles. Finally, we established a reverse-transduction pipeline based on vector pre-spotting in 96- or 384-well plates that facilitates high-throughput library panning. Our comprehensive illustration of the vast potential of alternative AAV capsids for peptide display should accelerate their in vivo screening and application as unique gene therapy vectors.